Vehicular noise assessment during the SARS COV-2 pandemic on some roads in the Gregorio Albarracín district, Tacna - Lazo Ramos, Richard Sabino (2022)
The objective of the research was to establish the sound pressure values in some roads of the Gregorio Albarracín district in the Tacna Region under conditions of vehicular restriction due to the measures adopted in the pandemic due to SARS COV-2. The study was carried out from the month of October to November 2020 using the methodology of the National Noise Monitoring Protocol (2013), establishing 63 measurement points that were located on Collpa, Humboldt, Municipal, La Cultura and Bohemia Tacneña avenues. Three measurements were recorded during rush hours of the day shift and one measurement during rush hours of the night shift for one week each month; adding a total of 3528 measurements. For this, the Type I AWA 6228 Sound Level Meter, certified by the National Institute of Quality (INACAL) was used. The results show that 82.2% of measurements during the day shift exceeded the values established in the Environmental Quality Standards (ECA) for noise (DSN° 085-2003-PCM), with a maximum value of 76.5 dBA for the residential area and during the night shift, 88.9% of the values exceeded the ECA, with a maximum value of 73.2 dBA recorded in the residential area. Finally, daytime and nighttime noise maps were prepared according to 5 noise levels, which allow us to geographically visualize the critical points of noise pollution in some roads of the Gregorio Albarracín district.